2010
DOI: 10.1007/s11661-010-0275-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Effect against Hydrogen Embrittlement

Abstract: The well-known term ''hydrogen embrittlement'' (HE) expresses undesirable effects due to hydrogen such as loss of ductility, decreased fracture toughness, and degradation of fatigue properties of metals. However, this article shows, surprisingly, that hydrogen can have an effect against HE. A dramatic phenomenon was found in which charging a supersaturated level of hydrogen into specimens of austenitic stainless steels of types 304 and 316L drastically improved the fatigue crack growth resistance, rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(63 citation statements)
references
References 51 publications
3
47
1
2
Order By: Relevance
“…The characteristic distribution of deuterium is considered to result from diffusion paths in the ferrite, as the diffusivity in the ferrite is known to be much higher in the ferrite than in the austenite. 40) It is noted that deuterium seems to be enriched in the ferrite side close to the interface between the ferrite and the austenite. Since the practical morphology of the interface is complicated, deuterium may be trapped in such complicated microstructure.…”
Section: Imaging Of Secondary Ions From Duplex Stainlessmentioning
confidence: 99%
“…The characteristic distribution of deuterium is considered to result from diffusion paths in the ferrite, as the diffusivity in the ferrite is known to be much higher in the ferrite than in the austenite. 40) It is noted that deuterium seems to be enriched in the ferrite side close to the interface between the ferrite and the austenite. Since the practical morphology of the interface is complicated, deuterium may be trapped in such complicated microstructure.…”
Section: Imaging Of Secondary Ions From Duplex Stainlessmentioning
confidence: 99%
“…The hydrogen content was estimated using the method described by Murakami et al in [10], which had shown satisfactory consistency with experimental data. The calculated values are presented in Table 1.…”
Section: Materials and Experimental Methodsmentioning
confidence: 93%
“…They can occur separately or in combination, so that different mechanisms can take the dominant role during crack initiation and crack growth. Most of the research on hydrogen embrittlement of stainless steels deals with the characterization of long fatigue crack growth behaviour [2,3] or the effect of hydrogen on monotonic properties obtained in tensile tests [4,5]. There is only little information available about the mechanisms of crack initiation and early crack growth.…”
Section: Introductionmentioning
confidence: 99%